Invasive species and endogenous risk - Finnoff, David; McIntosh, Chris; Shogren, Jason F.; Sims, Charles; Warziniack, Travis (Annual review of resource economics, 2010)
Invasive species policy is an economic issue. People affect the spread of invasive species, and these invaders affect people. This review discusses bioeconomic modeling using endogenous risk theory to capture the idea of jointly determined ecological and economic systems. This perspective adds precision to risk assessment and cost-benefit estimation. Bioeconomic modeling can help increase the chance of developing policies that promote better invasive species protection at lower cost. Several key points emerge. Differentiating between import- and export-related externalities determines the ability of agents to manage risk. A manager has four general economic strategies to mitigate invasive species risk and associated damages: prevention, eradication, control, and adaptation. When flexibility and timing play a critical role, a real options framework becomes the more appropriate analytical framework relative to traditional cost-benefit analysis. For many invasive species, valuation exercises will involve eliciting preferences to delay in the inevitable invasion and spread.
Gesehen am 25.04.2023